Consumer segmentation of green financial products based on sociodemographic characteristics - Sándor Gáspár; László Pataki; Ákos Barta; Gergő Thalmeiner; Zoltán Zéman (Journal of Risk and Financial Management, 2023)
Many green financial products currently have a low financial return level; even so, these products are spreading dynamically. In our study, we explored Hungarian green financial investment preferences and separated consumers of green financial products into homogeneous groups, which were characterized on the basis of sociodemographic characteristics. In the case of investments with a similar risk, using the sample we examined we proved that there is a homogenous group (C2) in Hungary which prefers green aspects to higher financial returns in the course of its investment decisions. We separated a group (C3) which can be considered influenceable, and we concluded that, with the application of appropriate marketing activities, this group could be a potential target consumers for national banks and traders of green financial products in the future. Young females are the main target consumers for green financial products in Hungary, and they are the largest majority of the C2 group, for whom financial rationality takes a backseat to green aspects. Based on the results of our study, national banks and traders of financial products can create a more accurate and effective marketing strategy for their products on the Hungarian market.
Keywords: 650; finance attitude; financial behavior; green finance; green investment; sustainability